The Study of Survey-design of Irrigation System Against Disasters in Kasi District, Vientiane Province: https://doi.org/10.69692/SUJMRD0901357 - PHILAKUNE, Souladeth; KHAMVONFSA , Viengthong; MAKEALOUN, Somyot (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study is to find the effect of the collapse of dams, canals and buildings in the rainy season that have had a natural effect in the past several years in order to find a long-term solution, by studying the results of the previous survey-design, which the results of this study found: the structure of the head system, the canal system and the buildings along the canal are not up to standard, so it is the cause of the collapse every year. Damaged. To be stronger, to use for a long time and to reduce the impact of disasters and to ensure the delivery of sufficient water in both seasons. To make the farmers in the area live better and to raise the productivity of agricultural production to meet the target of 4.5 tons per hectare.